2013
DOI: 10.1186/1751-0147-55-53
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic identification of streptococci and related bacteria isolated from bovine intramammary infections

Abstract: BackgroundStreptococcus spp. and other Gram-positive, catalase-negative cocci (PNC) form a large group of microorganisms which can be found in the milk of cows with intramammary infection. The most frequently observed PNC mastitis pathogens (major pathogens) are Streptococcus uberis, Strep. dysgalactiae, and Strep. agalactiae. The remaining PNC include a few minor pathogens and a large nonpathogenic group. Improved methods are needed for the accurate identification and differentiation of PNC.A total of 151 PNC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 30 publications
4
37
1
2
Order By: Relevance
“…agalactiae and 72% of CNS were identified by API system. The results tabulated in the current study, supported by similar and widespread data for clinical human and veterinary microbiology (Ilina et al, 2009;Lartigue et al, 2009; Science Publications Marklein et al, 2009;Nagy et al, 2009;Barreiro et al, 2010;Dubois et al, 2010;Ilina et al, 2010;Seibold et al, 2010;Moon et al, 2013;Raemy et al, 2013), confirmed that MALDI-TOF MS contributes in the fast identification of bacteria (one day versus five to eight days for conventional identification) and consequently the chance of an earlier treatment of subclinical and clinical mastitis with suitable antimicrobial agents will be carried out. In addition, in the dairy industry, MALDITOF MS can provides a faster, cheaper and more reliable identification of microorganisms isolated from milk of animals witth clinical and subclinical mastitis.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…agalactiae and 72% of CNS were identified by API system. The results tabulated in the current study, supported by similar and widespread data for clinical human and veterinary microbiology (Ilina et al, 2009;Lartigue et al, 2009; Science Publications Marklein et al, 2009;Nagy et al, 2009;Barreiro et al, 2010;Dubois et al, 2010;Ilina et al, 2010;Seibold et al, 2010;Moon et al, 2013;Raemy et al, 2013), confirmed that MALDI-TOF MS contributes in the fast identification of bacteria (one day versus five to eight days for conventional identification) and consequently the chance of an earlier treatment of subclinical and clinical mastitis with suitable antimicrobial agents will be carried out. In addition, in the dairy industry, MALDITOF MS can provides a faster, cheaper and more reliable identification of microorganisms isolated from milk of animals witth clinical and subclinical mastitis.…”
Section: Discussionsupporting
confidence: 65%
“…While ~ 95% of 39 isolates of S. aureus were properly detected by MALDI-TOF MS (only two strains produced weak signals in the mass spectrum, which led to failure of identification). According to the conditions of the current study, most spectral peaks noticed were in the mass range of m/z 2000-18000 Da, Similar ranges were noticed by (Barreiro et al, 2010;Raemy et al, 2013) who stated that the most spectral peaks resulted from analysis of protein samples were ranged from 2000 to 20000 Da mass range. The difference in mass range of spectra peaks might be due to the variation in techniques of sample preparation.…”
Section: Ajmsupporting
confidence: 61%
“…A 2013 study 61 supports the combination of conventional microbiology as first identification for triage and multiplex PCR use for rapid identification of bacteria associated with IMI. Molecular detection assays are a promising avenue in resolving false-negative issues, and several assays have already been developed that can provide solutions to this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectroscopy using the matrix-assisted laser desorption ionization-time of flight (MALDI-TOF MS) can also be performed to determine bacterial species 3,61 and bacterial strains 8 within a few minutes. 53 It is a reliable, easy to use, and cost-effective technique that has the potential to replace and/or complement conventional phenotypic identification, reaching sensitivity and specificity values of 100%.…”
Section: Identification Of Pathogens Causing Intramammary Infectionmentioning
confidence: 99%
“…The identities of these isolates were confirmed using Gram staining, oxidase test, catalase test and a serological assay. These same methods have been used for identification of Streptococcus species [33,34,35]. However, these tests are supplemented with molecular assays the isolates are identified at species level [35].…”
Section: Discussionmentioning
confidence: 99%